PENGARUH PENEMPATAN, KEADILAN ORGANISASIONAL, KEPUASAN KERJA TERHADAP KINERJA PEGAWAI RSUD WANGAYA KOTA DENPASAR - Meigantari, Ni Luh Gede Yuanda; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen, 2016)
The study aims to determine the placement, organizational justice and job satisfaction have a significant influence on the performance of employees at Regional General Hospital Wangaya. This research was conducted at the General Hospital of Wangaya with multiple linear regression analysis. The number of samples, by using the method of proportionate random sampling of 227 respondents. Results of the analysis showed that placement, organizational justice and job satisfaction positive and significant effect partially on the performance of employees, so management must look at education, knowledge, a person's experience, so it has good skills and personality in the services to the patients. Applying justice organizations by providing appropriate rewards and do not discriminate against employees in carrying out the work. Companies must pay attention to employees in terms of their needs and needs in the work, so that employees have the enthusiasm and excitement to finish the job to the fullest .
Keywords: placement, organizational justice, job satisfaction and performance